Metabolizable Energy of Crop Contents in Free-range Hens - Lomu, M. Amaka; Glatz, P.C.; Ru, Y.J. (International Journal of Poultry Science, 2004)
The composition and apparent metabolizable energy (AME) of the feed resources consumed by free-range layers was assessed by analyzing their crop contents. A chemical estimate of the AME of crop contents was 14.3 MJ/kg for hens not supplemented and 15.5 MJ/kg for hens given supplementary compound feed (on a dry matter basis). These values were considerably higher than the AME values estimated on crop contents based on ingredients visually identified in the crop (6.6 MJ/Kg with no supplement and 10.4 MJ/Kg with supplement). Further studies are required to refine the measurement of AME based on crop contents. Behaviour of free-range birds provided supplementary feed was compared to layers retained in an enclosure with no additional feed. Birds with access to the range had more (P<0.05) seeds and insects in their crops and exhibited greater (P<0.05) incidences of running, walking, and wing flapping reflecting greater freedom of movement. In the enclosure, birds engaged in more (P<0.05) scratching and foraging.